1995
DOI: 10.1073/pnas.92.17.7961
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal antiinflammatory drugs cause apoptosis and induce cyclooxygenases in chicken embryo fibroblasts.

Abstract: Programmed cell death (apoptosis) is an intrinsic part of organismal development and aging. Here we report that many nonsteroidal antiinflammatory drugs (NSAIDs) cause apoptosis when applied to v-src-transformed chicken embryo fibroblasts (CEFs). Cell death was characterized by morphological changes, the induction of tissue transglutaminase, and autodigestion of DNA. Dexamethasone, a repressor of cyclooxygenase (COX) 2, neither induced apoptosis nor altered the NSAID effect. Prostaglandin E2, the primary eicos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
1
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(98 citation statements)
references
References 27 publications
8
87
1
2
Order By: Relevance
“…Similarly, apoptosis was induced by indomethacin at a lower concentration than aspirin. These findings are consistent with those reported in colon cancer and other cell lines (Lu et al, 1995;Shiff et al, 1996). Apoptosis is often accompanied by growth arrest.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, apoptosis was induced by indomethacin at a lower concentration than aspirin. These findings are consistent with those reported in colon cancer and other cell lines (Lu et al, 1995;Shiff et al, 1996). Apoptosis is often accompanied by growth arrest.…”
Section: Discussionsupporting
confidence: 82%
“…The NSAID indomethacin, itself a peroxisome proliferator (44,45), completely inhibited PGE 2 synthesis at a dose of 10 M but required 500-1000 M to induce strong COX-2 expression. Induction of COX-2 by NSAIDS has been reported previously (49) and is consistent with the structural similarity between PPs and NSAIDS (44,45). Thus, COX-2 induction by PPs is probably not a consequence of inhibited prostaglandin synthesis, but rather is probably due to the activation of immediate-early signaling pathways (36).…”
Section: Figsupporting
confidence: 69%
“…Rather intriguingly, since COX inhibition has been brought in connection with increased COX mRNA expression, it seems that one or more COX-produced metabolites of AA must act in a negative feedback mechanism on COX [45]. Finally, studies investigating the nature of regulatory factors controlling COX-2 expression identified reactive oxygen species (ROS)-mediated nuclear factor-κB (NF-κB) activation to play an active role [46,47], suggesting a positive feedback mechanism between expression levels of NF-κB and COX.…”
Section: The Cox Pathwaymentioning
confidence: 99%